Disturbed glutathione antioxidative defense is associated with structural brain changes in neuroleptic-naïve first-episode psychosis patients. (September 2018) - Langbein, K.; Hesse, J.; Gussew, A.; Milleit, B.; Lavoie, S.; Amminger, G.P.; Gaser, C.; Wagner, G.; Reichenbach, J.R.; Hipler, U.-C.; Winter, D.; Smesny, S.
Abstract: Background: Oxidative stress and impaired antioxidant defense are reported in schizophrenia and are thought to be associated with disturbed neurodevelopment, brain structural alterations, glutamatergic imbalance, negative symptomatology, and cognitive impairment. To test some of these assumptions we investigated the glutathione (GSH) antioxidant defense system (AODS) and brain structural abnormalities in drug-naïve individuals with first acute episode of psychosis (FEP). Method: The study involved 27 drug-naïve FEP patients and 31 healthy controls (HC). GSH AODS markers and TBARS (thiobarbituric acid reactive substances) were measured in blood plasma and erythrocytes. High-resolution T1 -weighted 3T MRI were acquired from all subjects. To investigate brain structural abnormalities and effects of illness on interactions between GSH metabolites or enzyme activities and local grey matter density, voxel-based morphometry (VBM) with the computational anatomy toolbox (CAT12) was used. Symptomatology was assessed using the Positive and Negative Syndrome Scale (PANSS) and the Symptom Checklist 1990 revised (SCL-90-R). Results: (i) In FEP patients, glutathione reductase activity (GSR) was lower than in the HC group. GSR activity in plasma was inversely correlated with SCL-90-R scores of depression and PANSS scores of the negative symptom subscale. (ii) A reduction of GM was observed in left inferior frontal, bilateral temporal, as well as parietal cortices of FEP patients. (iii) Interaction analyses revealed an influence of illness on GSR/GM associations in the left orbitofrontal cortex (BA 47). Conclusion: Our findings support the notion of altered GSH antioxidative defense in untreated acute psychosis as a potential pathomechanism for localized brain structural abnormalities. This pathology relates to a key brain region of social cognition, affective motivation control and decision making, and is clinically accompanied by depressive and negative symptoms. Highlights: Alterations of the glutathione AODS are associated with brain structural abnormalities in drug-naïve FEP patients. The effect of illness on associations between GSR activity and grey matter density relates to the left orbitofrontal cortex. Glutathione reductase activity in FEP patients was associated with negative symptoms.